Liquid chromatographic method for simultaneous estimation of anti‐hypertensive drug combination Azilsartan Medoxomil and Cilnidipine. Issue 4 (19th February 2023) - Solanki, Dhavalsinh P.; Panday, Vishal R.; Shah, Dimal A.; Chhalotiya, Usmangani; Tandel, Jinal N.; Kacchiya, Heta M.
Abstract: A combination of Azilsartan Medoxomil and Cilnidipine is prescribed in the treatment of Hypertension. An accurate and precise high‐performance liquid chromatographic method has been developed for the estimation of Azilsartan Medoxomil and Cilnidipine in a combined tablet dosage form. Symmetry C18 (250 × 4.6 mm, 5 μm) column was used as the stationary phase, and methanol:water (85:15 v/v; pH 3.5) was used as the mobile phase. The method was linear in the concentration range of 4–20 μg/ml for Azilsartan Medoxomil and 1–5 μg/ml for Cilnidipine with a correlation coefficient ( r 2 ) 0.995 for Azilsartan Medoxomil and 0.995 for Cilnidipine. The proposed method was validated with respect to linearity, accuracy, precision, and robustness as per International Council on Harmonization Q2 (R1) guideline. A forced degradation study was performed to find out the intrinsic stability of the molecules. The degradation products were well resolved from the drug peak and did not interfere with the analysis. The method was successfully applied for the analysis of Azilsartan Medoxomil and Cilnidipine in combined tablet formulation.